Antimicrobial and resource utilization with T2 magnetic resonance for rapid diagnosis of bloodstream infections: systematic review with meta-analysis of controlled studies. (4th May 2021) - Giannella, Maddalena; Pankey, George A.; Pascale, Renato; Miller, Valerie M.; Miller, Larry E.; Seitz, Tamara
ABSTRACT: Objectives: To compare antimicrobial and resource utilization with T2 Magnetic Resonance (T2MR) versus blood culture (BC) in patients with suspected bloodstream infection. Methods: We systematically searched MEDLINE, EMBASE, and CENTRAL for randomized trials or observational controlled studies of patients with suspected bloodstream infection receiving a diagnosis with T2MR or BC. Using an inverse variance meta-analysis model, we reported mortality using the risk ratio (RR) and the remaining outcomes as the mean difference (MD). Results: Fourteen studies were included in the meta-analysis. Time to detection (MD = −81 hours; p < 0.001) and time to species identification (MD = −77 hours; p < 0.001) were faster with T2MR. Patients testing positive on T2MR received targeted antimicrobial therapy faster (−42 hours; p < 0.001) and patients testing negative on T2MR were de-escalated from empirical therapy faster (−7 hours; p = 0.02) vs. BC. Length of intensive care unit stay (MD = −5.0 days; p = 0.03) and hospital stay (MD = −4.8 days; p = 0.03) were shorter with T2MR. Mortality rates were comparable between T2MR and BC (28.9% vs. 29.9%, RR = 1.02, p = 0.86). Conclusion: Utilization of T2MR for identification of bloodstream pathogens provides faster time to detection, faster transition to targeted microbial therapy, faster de-escalation of empirical therapy, shorter ICU and hospital stay, and with comparable mortality rate versus BC.